Variabilidade da atividade do elemento de transposição mariner em populações naturais de Drosophila simulans - Jardim, Sinara Santos (2012)
Transposition elements (TEs) are DNA sequences with the ability to move from one chromosome region to another. These elements have different mechanisms of transposition and diversity in their sequences, giving them wide distribution among most organisms. The DNA transposon mariner is found in a range of bodies, being ubiquitous in eukaryotes and is excellent for studying the behavior of TE within natural populations of Drosophila. Among the natural populations of D. simulans there are variations in the number of copies of mariner and, hence, in its activity. But within a same population such variations are scarcely assessed. To estimate the activity in natural populations of D. simulans, crosses were made between these and the mutant strain, D. simulans white-peach. The F1 males have spots in the eyes that indicate reversion to the wild condition in a white-peach context, which are used to estimate the activity. In this work, isofemale strains were prepared from recently collected natural populations and from strains maintained in the laboratory. The variables assessed the activity within and between isofemale strains. The number of spots in F1 revealed how many transposition events occurred, and there was no difference in variances between the isofemale strains of the same collection site. The area of the spots showed in what phase of development transposition occurred more frequently. In the test experiment, the embryo stage showed the large patches. Blotches indicated that mobilization occurred in the early stages of cellular determination. In crosses between the evaluated isofemale strains and the white-peach strains, mobilization occurred at all stages of development. Molecular analysis of the copies by qPCR showed variation. But there was no correspondence between the high number of copies and patches most isofemale strains. These differences may be due to a single highly active element or of many elements with low activity. Some already described mariner regulation mechanisms may be acting in isofemale strains evaluated by inhibiting or decreasing the activity of some copies. Additional analyses are also needed to investigate how many copies are actually active in the genome of natural and recently collected strains.